PENGEMBANGAN MODUL BIOLOGI MATERI ANIMALIA MELALUI PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI - SIPAHELUT, CORNELIA (Jurnal Ilmu Pendidikan Indonesia, 2020)
This study aims to develop a problem-based biology module to improve higher-order thinking skills in Animalia material. The design used is an equivalent type of pre test post test design. The research sample consisted of 32 students of class X SMA Negeri 1 Sentani who used modules. The results showed that the use of modules can improve high-order thinking skills and the overall average n-Gain is 0.73 with high categories.